1966
DOI: 10.1037/h0023153
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and treatment factors modifying the postisolation syndrome in dogs.

Abstract: Social and manipulative behavior in postisolation Ss observed from Weeks 16-19 was reduced compared with Ss with equal experience spread over Weeks 4-19. Chlorpromazine aided socialization when combined with pretest handling but not without pretest handling. Terriers were less vulnerable than beagles to the postisolation syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…These groups are also most differen t from the control-control group. Such a "c ontrast" effect appears to be fully in agreement with the suggestion put forward by Fuller and Clark (1966) that the effects produced in dogs by restricted early experience may be mainly due to the trauma of emerging from one kind of environm ent and ente ring anothe r that is strikingly different. In the present study, the analogous contrast would lie in the transition from occupying a "quiet" uterine environment to rearing by an " active" mother and vice versa.…”
Section: Discussionsupporting
confidence: 78%
“…These groups are also most differen t from the control-control group. Such a "c ontrast" effect appears to be fully in agreement with the suggestion put forward by Fuller and Clark (1966) that the effects produced in dogs by restricted early experience may be mainly due to the trauma of emerging from one kind of environm ent and ente ring anothe r that is strikingly different. In the present study, the analogous contrast would lie in the transition from occupying a "quiet" uterine environment to rearing by an " active" mother and vice versa.…”
Section: Discussionsupporting
confidence: 78%
“…With varying degrees of social isolation, particularly during the critical period for socialisation (4-12 weeks of age), dogs are likely to develop maladaptive behaviours such as kennel dog syndrome (Scott and Fuller, 1965 ) or the more severe isolation syndrome (Fuller and Clark, 1966 ). It has also been shown that dogs' activity patterns are strongly influenced by the presence of humans (Neamand et al, 1975: Hughes andCampbell, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Although the reasons for the species difference i n results are unknown, it is obvious that the influence of early experience, e.g., AMPH treatment, on adult behavior varies with the genetic background of the animals tested. This generalization is supported by the efforts of several workers including Fuller and Clark (1966), who reported that early isolation affects the adult behavior of two breeds of dogs in a differential manner; Levine and Broadhurst (1963), who found that the effect of controlled infantile stimulation on adult performance varies considerably in two strains of rats that show genetic differences in emotionality; and Winston (1963), who demonstrated that hereditary factors and infantile experience have an important influence on learning in adult mice.…”
Section: Discussionmentioning
confidence: 82%